Investigation of Circulating anti- Coxsackie B, anti- Polio and anti- Adeno IgG in newly diagnosed T1DM Children - Saleh, Eman M.; mohymen, Nidhal abdul (Journal of the Faculty of Medicine Baghdad, 2008)
Back ground: Viruses may be involved in the pathogenesis of Type 1 Diabetes Mellitus (T1DM), either through direct β-cell infection or as triggers of autoimmunity. Objective: To investigate the presence of specific anti- viral IgG antibodies for Coxsackie virus type B (CVB5), Poliovirus, and Adenovirus which proposed to be involved in the etiology of T1DM. Subjects & methods: A total of 60 Iraqi T1DM children were included in the presents study. They were new onset of the disease (diagnosis was from one week up to five months). For the purpose of comparisons, 50 apparently healthy control subjects were selected. Serum IgG against Coxsackie virus type B5, Adenovirus type 3, 4, and 7, and Poliovaccin Trivalent were detected quantitatively with an indirect ELISA. Results: High proportion of anti-CVB5 IgG (20%)(p<0.05) and anti- Polio IgG (31.67%) were found in T1DM children compared to controls (8%, 26% respectively), while anti- Adeno IgG were detected in diabetic patients only (6.67%)(p<1.0001).